2017
DOI: 10.1002/ajh.24819
|View full text |Cite
|
Sign up to set email alerts
|

Impact of comorbidities on outcomes of elderly patients with diffuse large B‐cell lymphoma

Abstract: International prognostic index (IPI) has remained the primary prognostic tool in diffuse large B cell lymphoma (DLBCL) for more than 20 years. Even though the disease is more common in older population, the impact of comorbidities, dose reductions, and treatment-related adverse events (TAEs) on the outcome in elderly DLBCL patients has not been well established. We studied 413 consecutive patients aged ≥ 60 years who were treated at the Cleveland Clinic. The median age at diagnosis was 69 years, 58% of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
33
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 22 publications
7
33
1
1
Order By: Relevance
“… did not find evidence for an association between CCI and choice of chemotherapy regimen or completion of treatment in their review. However, they confirm findings from several prior studies, restricted to patients who have received treatment, that CCI is associated with a higher frequency of grade III/IV toxicities, dose reductions and in the majority of studies, with inferior OS []. In line with this, the increased risk of other‐cause death associated with comorbidity amongst patients treated with curative intent in our study may be due to aggravation of prior conditions by toxic treatment regimens.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“… did not find evidence for an association between CCI and choice of chemotherapy regimen or completion of treatment in their review. However, they confirm findings from several prior studies, restricted to patients who have received treatment, that CCI is associated with a higher frequency of grade III/IV toxicities, dose reductions and in the majority of studies, with inferior OS []. In line with this, the increased risk of other‐cause death associated with comorbidity amongst patients treated with curative intent in our study may be due to aggravation of prior conditions by toxic treatment regimens.…”
Section: Discussionsupporting
confidence: 92%
“…The inferior overall survival amongst comorbid patients in this large cohort is in line with several prior studies []. Few prior studies have however assessed the influence of comorbidity on choice of treatment with palliative or curative intent as the majority of prior studies on comorbidity in DLBCL have been restricted to patients who have received chemotherapy . In our study, the inferior outcome was mainly due to increased other‐cause mortality amongst curatively treated comorbid patients, and by an increase in both lymphoma‐specific and other‐cause death amongst all comorbid patients, largely explained by the lower relative probability of receiving treatment with curative intent amongst patients with CCI ≥ 1.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Treatment of DLBCL in older patients is impacted not only by comorbidities, but also by performance and functional status. We found that patients with a CCI of 2+ had shorter two-year OS, similar to other studies in which having a high CCI (≥3) was predictive of outcome including PFS and OS [71,72]. The importance of incorporating information from a comprehensive geriatric assessment in initial treatment decisions for older/less fit patients has also been recognized [73][74][75][76][77][78][79][80][81][82].…”
Section: Discussionsupporting
confidence: 86%
“…The negative prognostic impact of comorbidities is well established for non-Hodgkin lymphoma patients overall (Wieringa et al, 2014;Saygin et al, 2017;Antic et al, 2018;Wasterlid et al, 2018). For example, in a study of 962 diffuse large B-cell lymphoma (DLBCL) patients, a high comorbidity score was independently associated with a threefold increased risk of death (Antic et al, 2018), and among elderly patients comorbidity had a better discriminative power than the International Prognostic Index (IPI).…”
Section: Introductionmentioning
confidence: 99%